If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5x + 6)(x + -1) + -1(2x + -5x + 3) = 0 Reorder the terms: (6 + 5x)(x + -1) + -1(2x + -5x + 3) = 0 Reorder the terms: (6 + 5x)(-1 + x) + -1(2x + -5x + 3) = 0 Multiply (6 + 5x) * (-1 + x) (6(-1 + x) + 5x * (-1 + x)) + -1(2x + -5x + 3) = 0 ((-1 * 6 + x * 6) + 5x * (-1 + x)) + -1(2x + -5x + 3) = 0 ((-6 + 6x) + 5x * (-1 + x)) + -1(2x + -5x + 3) = 0 (-6 + 6x + (-1 * 5x + x * 5x)) + -1(2x + -5x + 3) = 0 (-6 + 6x + (-5x + 5x2)) + -1(2x + -5x + 3) = 0 Combine like terms: 6x + -5x = 1x (-6 + 1x + 5x2) + -1(2x + -5x + 3) = 0 Reorder the terms: -6 + 1x + 5x2 + -1(3 + 2x + -5x) = 0 Combine like terms: 2x + -5x = -3x -6 + 1x + 5x2 + -1(3 + -3x) = 0 -6 + 1x + 5x2 + (3 * -1 + -3x * -1) = 0 -6 + 1x + 5x2 + (-3 + 3x) = 0 Reorder the terms: -6 + -3 + 1x + 3x + 5x2 = 0 Combine like terms: -6 + -3 = -9 -9 + 1x + 3x + 5x2 = 0 Combine like terms: 1x + 3x = 4x -9 + 4x + 5x2 = 0 Solving -9 + 4x + 5x2 = 0 Solving for variable 'x'. Factor a trinomial. (-9 + -5x)(1 + -1x) = 0Subproblem 1
Set the factor '(-9 + -5x)' equal to zero and attempt to solve: Simplifying -9 + -5x = 0 Solving -9 + -5x = 0 Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + -5x = 0 + 9 Combine like terms: -9 + 9 = 0 0 + -5x = 0 + 9 -5x = 0 + 9 Combine like terms: 0 + 9 = 9 -5x = 9 Divide each side by '-5'. x = -1.8 Simplifying x = -1.8Subproblem 2
Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1Solution
x = {-1.8, 1}
| X^3=36 | | 2n^3+7=2n^5 | | 140-7x=38x+15 | | 5n+7=27 | | (n-6)*2=4 | | (n-6)*10=70 | | 65=-4(5b+3) | | 108-3x=4x+17 | | 14-6x=6-8x | | 7(2y-3)=28 | | 8x^3+4x^2-34x+15=0 | | -3(4-2w)=10 | | 3(4-3s)=34 | | 3g+15=5g-3 | | 9x+23=3x+197 | | -3(4-2n)=19 | | -3(4-2)=19 | | 2x+3=2(2x+7) | | 5x+26=15x-64 | | x*x=x | | x+2x-3x+4x-5x=-5 | | 2x^2-4kx+k=0 | | 9x^4-3x^2+1= | | 3x*2+5x+3=0 | | 2(x+1)-(x+2)=3 | | 2(x+1)-(x-2)=3 | | 72-3x=6x+24 | | 25xsomthing=105 | | 0.25(2-x)=9 | | 3(2x+5)=29-x | | 21=0.3(3-4x) | | 21=0.3(3-4) |